Семантическая сочетаемость слов со значением “совокупность множества” в современном английском языке - Астраускайте, Даля (Kalbotyra, 1985)
The aim of the present article is to investigate the semantics of the nouns expressing a united multitude of certain objects (company, crew, bunch, flock, etc.) on the syntagmatic level. The author proceeds from the assumption that these nouns may be singled out into a separate semantic group on the basis of the semantic components “joint” and “multitude”. The analysis carried out shows that this semantic component may be explicated on the syntagmatic level. Grammatically this may be achieved by the absence of grammatical concord between the noun and the verb (or pronoun). On the semantic level the noun may enter into semantic concord with other words having the same semantic component.